HUBUNGAN SIKAP KERJA DENGAN KEJADIAN NYERI TANGAN PADA PEKERJA BATIK TULIS DI DESA TRUSMI PLERED KABUPATEN CIREBON - Mitha Erlisya Puspandhani; Aldi Fadilah; Ahmad Syaripudin (LPPM ITEKES Mahardika, 2018)
Background: Body posture in the working position is a picture of the position of body, head and limbs (arms and legs) other, a way of working that is not ergonomic can cause variety health disorders that is movement disorders in certain body parts such as hands or called musculoskeletal. Based on preliminary study 6 out of 10 batik workers experience hand pain with 60% percentage. The purpose of this research to determine the relationship of work attitude with the incidence of hand pain on batik workers at the Village Trusmi Plered Cirebon. Method: Type of descriptive correlation research with cross sectional study research Samples taken in random sampling that is many as 86 workers batik workers. The instruments used in this study are REBA Observation and simple descriptive scale pain. Univariate data analysis with percentage and bivariate analysis with Rank Spearmen. Result: The result showed that from 86 respondents 69 respondents with upper arm motion 450 1. 900 flexion with percentage (80,2%) and 64 respondent with percentage (74,4%) experience hand pain and Spearman rank test results showed a positive correlation of 0.27 with a low correlation so there is work attitude relation at Batik workers with the incidence of hand pain on batik workers with upper arm position (ρ value 0.011, α = 0.1) Suggestion: It is expected that batik managers pay attention to the workplace design in accordance with the work position of respondents in accordance with the body position for ergonomics.